1996
DOI: 10.1016/0042-6989(95)00286-3
|View full text |Cite
|
Sign up to set email alerts
|

Illumination, Shading and the Perception of Local Orientation

Abstract: We investigated the perception of local surface orientation on a simple smooth object, under several different illumination conditions. The perceived local orientation was determined for several points on the surface and quantified as slant and tilt of the local tangent plane. We found an underestimation of the perceived slant and a larger variance for the perceived tilt than for the perceived slant. We found also that subjects were less biased at estimating the surface orientation when the shape was locally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 36 publications
5
28
0
Order By: Relevance
“…In our results, these thresholds correspond to approximately 15 • − 25 • of the ground truth slant with the exception of the south sector. Mamassian and Kersten [21] expect this threshold to be approximately 20 • which is consistent with our finding of 15 • − 25 • .…”
Section: Analysis Of the Perceived Surface Slantsupporting
confidence: 82%
See 2 more Smart Citations
“…In our results, these thresholds correspond to approximately 15 • − 25 • of the ground truth slant with the exception of the south sector. Mamassian and Kersten [21] expect this threshold to be approximately 20 • which is consistent with our finding of 15 • − 25 • .…”
Section: Analysis Of the Perceived Surface Slantsupporting
confidence: 82%
“…The division into subintervals was selected on a priori grounds. According to previous evidence [21] and also concluding from our own analysis, the underestimation of slant is zero at ca. 20 • of ground-truth slant and highest for slants 40 • − 60 • (see also Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mamassian and Kersten demonstrated that the occluding contour of an object can be a significant cue to surface orientation [Mamassian and Kersten 1995]. In their experiment, subjects were instructed to orient a gauge figure to estimate local surface orientation for an object that is shaded under various lighting conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have investigated how lighting and shading affect shape perception [Mamassian and Goutcher 2001;Mamassian and Kersten 1995;Koenderink et al 1996;Langer and Bulthoff 2001], yet none have specifically examined variations in the slant of light.…”
Section: Introductionmentioning
confidence: 99%